2019
DOI: 10.1530/eje-18-0818
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and prevalence of diabetes and insulin resistance in the Spanish population: Di@bet.es study

Abstract: Objective The activity of brown adipose tissue is sensitive to changes in ambient temperature. A lower exposure to cold could result in an increased risk of developing diabetes at population level, although this factor has not yet been sufficiently studied. Design We studied 5072 subjects, participants in a national, cross-sectional population-based study representative of the Spanish adult population (Di@bet.es study). All subjects underwent a clinical, demographic and lifestyle survey, a physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Finally, the current study revealed how cardiovascular disease risk factors were related to regional environmental and socioeconomic characteristics. In addition to pre vious individuallevel evidence across ethnicities, [17][18][19] our findings suggest that the associations might be more complex. Indeed, temperature was negatively associated with blood pressure and positively associated with blood glucose.…”
Section: E N T R a L C H I N A E A S T C H I N A N O R T H C H I N A ...mentioning
confidence: 55%
“…Finally, the current study revealed how cardiovascular disease risk factors were related to regional environmental and socioeconomic characteristics. In addition to pre vious individuallevel evidence across ethnicities, [17][18][19] our findings suggest that the associations might be more complex. Indeed, temperature was negatively associated with blood pressure and positively associated with blood glucose.…”
Section: E N T R a L C H I N A E A S T C H I N A N O R T H C H I N A ...mentioning
confidence: 55%
“…Elevated brown adipose tissue activity has been linked with improved glycaemic control and insulin sensitivity in both healthy individuals and patients with type 2 diabetes [68][69][70] . At the population level, high mean annual temperature was associated with elevated fasting plasma glucose levels, insulin resistance, and increased incidence and prevalence of diabetes [71][72][73] (Supplementary Table 1). Short-term fluctuations in temperature have also been linked with blood pressure levels.…”
Section: [H2] Epidemiology Of Temperature-related Cvdmentioning
confidence: 99%
“…Analysing worldwide data for the prevalence of diabetes, as diagnosed by fasting blood glucose ≥7.0 mmol/l or medication for elevated blood glucose levels, the same authors found an association between mean annual temperature and country-wise age-, sex-, income- and obesity-adjusted prevalence of increased fasting blood glucose levels [ 35 ]. In accordance, ambient temperature was associated with the prevalence of dysglycaemia and insulin resistance in a cohort of Spanish adults [ 36 ]. The increase in fasting blood glucose levels and insulin resistance with increased ambient temperatures may be partially mediated by differences in type and frequency of physical activity, which varies with different seasons and environmental temperatures [ 37 ].…”
Section: Heatmentioning
confidence: 91%